Comprehensive Review of Nursing Leadership and Strategies for Managing Healthcare Teams in Dynamic Environments - Al-Ghamdi, Nisreen Mohammed Abdullah; Aljaziri, Marwa jafar Mohammed; Alshahrani, Aisha Amer Mohammed; Al-Ghamdi, Noura Mosaed Mohammed; Al-Omari, Ezzah Ahmed; Al-Nassar, Maryam Abdulaziz Yousef; Al Qawan, Hamad Salem; Al-Bishi, Munira Saad Abdullah; Al-Bishi, Sarah Saad Abdullah; Al-Aklabi, Rabia Hamdan Bakhit (Journal of Ecohumanism, 2024)
The healthcare environments are becoming more complex, and it is impossible to lead a team and provide the needed quality of care without the necessary leadership skills. This review aims to provide nursing leadership approaches to managing healthcare teams: leadership behaviors, communication, conflict, and flexibility. A combination of qualitative and quantitative research design systems was used in the synthesis of literature and case analysis, and a special focus was placed on the effects of transformational leadership on the performance of teams. The study also re-emphasizes the importance of flexible leadership in enhancing outcomes, particularly during calamities. Recommendations include management development, an educational infrastructure, and proper institutional policies. The findings presented in this paper can be useful to nurse leaders in managing the challenges faced in today’s diversified hospitals